The role of pannexin channels in small arteries - Mokori, E.B. (2016)
Pannexins (Panx) are membrane bound channels which allow the exchange of molecules, particularly ATP, between the cytoplasm and the extracellular space. Panx channels have been shown to be expressed in the vasculature, and there is evidence suggesting that they are involved in the regulation of vasoconstriction in small arteries. In mice thoracodorsal resistance arteries Panx1 channels are co localized with α1D-adrenoceptors on smooth muscle cells, and have been reported to open after α1D-adrenoceptor stimulation to release ATP which is then responsible for causing vasoconstriction by activating P2 purinoceptors (Billaud et al., 2011). This thesis examined the expression and the role of Panx channels in rat mesenteric and cerebral arteries.